Effect Of Delirium Care Bundle On ICU Acquired Delirium Patients With A Mechanical Ventilator. A Randomized Controlled Trial (RCT) (Journal of Pharmaceutical Negative Results, 2022)
IntroductionDelirium is frequently unrecognized or missed despite of it’s high incidence and prevalence that leads to poor clinical outcomes and an enormous rise in cost by ameliorating morbidity, mortality, and hospital and ICU length of stay. Delirium bundle care (ABCDEF bundle) finds to be an evidence-based effective strategy for health care professionals to manage and enhance patient recovery and health outcomes related to delirium in ICU.Objective The primary aim of the study is to determine the effectiveness of a delirium care bundle among 56 mechanically ventilated ICU acquired delirium patients with routine care in intensive care units at selected hospitals in Kerala, India.Materials and methodsA randomized controlled trial was conducted to implement a delirium care bundle intervention. Total fifty-six mechanically ventilated ICU acquired delirium patients were recruited using inclusion and exclusion criteria. The ABCDEF bundle has been implemented every day for the first seven days of ICU admission, and patient delirium status was assessed using the Confusion Assessment Method for The Intensive Care Unit (CAM-ICU). Statistical analysis was done by using SPSS 20.0 version.ResultsDelirium care bundle intervention has been marked to have a significant effect on patient delirium status. It has been manifested that number of days with delirium was significantly dwindled by 2.3 days (4.1 ± 2.1, p=0.001), duration of patients stay with mechanical ventilation was declined by nearly 2.12 days, patients aided on ventilation were a minimum of 3 days and a maximum of 5 days (4.01 ± 0.83, p=0.001), length of ICU stay was decreased nearly 2.41 days (7.31 ± 2.71, p=0.001). The length of hospital stay was curtailed by nearly 2.54 days (10.78 ± 3.87, p=0.001) compared with the control group.Conclusion Implementing a standard delirium care bundle among mechanically ventilated patients with ICU acquired delirium has notably condensed the adverse effects of delirium, and it’s risk factors, alongside it also turned down the patient morbidity and mortality rate